1998
DOI: 10.1104/pp.118.3.975
|View full text |Cite
|
Sign up to set email alerts
|

Drying Increases Intracellular Partitioning of Amphiphilic Substances into the Lipid Phase

Abstract: Previously we proposed that endogenous amphiphilic substances may partition from the aqueous cytoplasm into the lipid phase during dehydration of desiccation-tolerant organ(ism)s and vice versa during rehydration. Their perturbing presence in membranes could thus explain the transient leakage from imbibing organisms. To study the mechanism of this phenomenon, amphiphilic nitroxide spin probes were introduced into the pollen of a model organism, Typha latifolia, and their partitioning behavior during dehydratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Our best speculation builds on recent ideas of partitioning of amphiphilic molecules and surface-active agents into hydrophilic or hydrophobic regions depending on water content (Golovina et al 1998;Hoekstra et al 1999). Within the triacylglycerol fraction, amphiphilic molecules may catalyze or inhibit crystallization reactions (see Walters et al 2005a), thereby explaining differences in crystallization rate, but not total crystallization, with seed water content (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Our best speculation builds on recent ideas of partitioning of amphiphilic molecules and surface-active agents into hydrophilic or hydrophobic regions depending on water content (Golovina et al 1998;Hoekstra et al 1999). Within the triacylglycerol fraction, amphiphilic molecules may catalyze or inhibit crystallization reactions (see Walters et al 2005a), thereby explaining differences in crystallization rate, but not total crystallization, with seed water content (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…However, in these studies no explanation of the phenomenon of pollen injuries was proposed. Investigations of Hoekstra et al (1992), Wolkers and Hoekstra (1995) and Golovina et al (1998) showed that cytoplasmic membranes were prime targets for destructive changes in pollen grains as a result of abiotic stresses. There is little information in the literature about the structural and biophysical function of membranes in the tolerance of pollen grains to industrial pollution.…”
Section: Discussionmentioning
confidence: 99%
“…This leakage is generally transient and does not lead to severe damage (Senaratna and McKersie, 1983;Hoekstra and Van der Wal, 1988). Lately, this leakage has been attributed to the transiently increased membrane permeability associated with the presence, in plasma membranes, of amphiphilic metabolites that are in the process of partitioning back into the aqueous cytoplasm during rehydration (Golovina et al, 1998). Complete loss of cell viability due to irreversible membrane damage may occur when dried anhydrobiotic cells are allowed to imbibe in relatively cold media (Hoekstra et al, 1999).…”
Section: Introductionmentioning
confidence: 99%